ENERGI DAN ZAT GIZI DALAM PENYELENGGARAAN MAKANAN DI TAMAN KANAK-KANAK DAN PERBANDINGANNYA TERHADAP SUBJEK TANPA PENYELENGGARAAN MAKANAN - Nurhidayati, Vieta Annisa; Martianto, Drajat; Sinaga, Tiurma (Jurnal Gizi dan Pangan, 2017)
The purpose of this study is to calculate the contribution of nutrient availability in kindergarten food service to the fulfillment of energy and nutrient requirements as well as to analyze the difference in energy and nutrient adequacy level of food consumption in a day between samples with and without food service. The study used comparative cross sectional study design with total of 80 samples that were divided into two groups by with and without food service. Consumption data of the samples were collected with a food recall method. Nutrients that meet the standards adequacy of nutrients in the menu was just calcium by 64.6% of availability. There was no difference in the level of adequacy of energy, protein, fat, carbohydrates, calcium, and vitamin C in both groups (p>0.1), but differences in the level of adequacy of iron in both groups (p<0.1) was found.